KOH for enhanced sugarcane bagasse delignification and further production of sugar-rich hydrolyzates by enzymes application - Paixão Alves, Susana (2015)
Lignocellulosic biomass is envisaged as an important raw material for bioethanol production due to its low cost and high availability. Sugarcane bagasse (SCB), a fibrous residue of cane stalks left over after crushing and extraction of the juice from sugarcane; it is one of the largest cellulosic agro-industrial by-products. Tons of SCB are produced in Brazil as a waste of sugar and ethanol industries. This lignocellulosic by-product is a potential renewable source for 2G-bioethanol production. Usually, SCB is pretreated using alkaline and/or acid treatments viewing higher ethanol yields. The main goal of this study was to optimize the delignification of SCB towards the higher availability of glucans and xylans for further enzymatic hydrolysis to obtain sugar-rich syrups that will be more readily fermented to bioethanol. The delignification was carried out by autoclaving the biomass with KOH and the influence of KOH concentration (1-10%) and the autoclave time (10-60 min) were evaluated through a statistical design. Experimental distribution for two factors according to the Doehlert uniform design was used to produce response surfaces. The responses studied in this design were the percentage of hemicellulose, lignin and total polysaccharides. The results showed that from the two factors evaluated, the KOH concentration was the one that most influenced the response observed and that the treatments of SCB with KOH 5-10% for 35 minutes of autoclave at 121ºC and 1 atm led to the highest rates of lignin extraction. Using KOH treatment, a significant reduction of lignin content in SCB was observed, namely from 19% to 5%. Scanning electron micrographs of SCB pre-treated with 10% KOH for 35 minutes demonstrated a change in the structure of the material, with the appearance of broken structures, which can be attributed to the alkaline treatment. To validate the experiments, the SCB pretreated in the optimal conditions (95% of total polysaccharides) was further hydrolyzed with commercial enzymes and the enzymatic hydrolysis performance was evaluated.